Analisa Pemborosan dengan Lean Distribution dan Perbaikan dengan Failure Mode and Effect Analysis di Perusahaan Logistik PT. XYZ - Siburian, Timothy H; Sumiati, Sumiati (Universitas Batanghari Jambi, 2025)
This study aims to analyze waste through lean distribution and improve it through Failure Mode and Effect Analysis (FMEA) at the logistics company PT. XYZ. The method used in this study is Failure Mode and Effect Analysis (FMEA). The results of this study concluded that the most frequent waste was in waiting and transportation. After being given suggestions for improvements, the process time was reduced from 306 minutes to 236 minutes.